Comparative legal history - Tomlins, Christopher; Boalt, Elizabeth Josselyn; Edward Elgar Publishing (Cheltenham, UK : Edward Elgar Publishing Limited, 2021)
This research review has been written to serve two purposes. The first is to explain the coming-to-be of comparative legal history as a scholarly practice in both its European and its extra-European emphases. The second is to present exemplary research representing not only the comparative perspective's concrete achievements to date, but also, and more pronouncedly, to stimulate the scholarly imagination. The review selects a key sampling of texts, which demonstrate how comparative legal history may be pursued and what it may achieve.
28.Jo-Anne Claire Pemberton (2013), 'The So-Called Right of Civilisation in European Colonial Ideology, 16th to 20th Centuries', Journal of the History of International Law, 15, 25-52[28] -- 29.Sundhya Puja (2013), 'Laws of Encounter: A Jurisdictional Account of International Law', London Review of International Law, 1 (1), 63-98[36] -- 30.Jakob Zollman (2014), 'German Colonial Law and Comparative Law, 1884-1919', in Thomas Duve (ed.), Entanglements in Legal History: Conceptual Approaches, Frankfurt, Germany: Max Planck Institute for European Legal History, 253-94[42] -- 31.Binyamin Blum (2017), 'The Hounds of Empire: Forensic Dog Tracking in Britain and Its Colonies, 1888-1953', Law and History Review, 35 (3), 621-65[45].
The recommended readings are available in the print version, or may be available via the link to your library's holdings.
Includes bibliographical references and index.
Keywords: Comparative law; Comparative law -- Methodology; Law -- History; porovnávacie právo; právo; elektronické dokumenty